Signs, Intentionality, and Imaginability : Selected Papers - Ruthrof, Horst, (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
This book contains essays by Horst Ruthrof, tracing the author's intellectual history from his encounter with literature to his critique of the philosophy of language. If you have ever felt that our linguistic and philosophical approaches to language lack an explanation of what renders it so powerful, you share the author's motivation for writing these essays. With tools from Locke, Kant, Peirce, and especially Husserl, the author redefines natural language as "a set of social instructions for schematically imagining, and acting in, a world" and gradually identifies what grants natural language its power: imaginability .